PENGARUH pH DAN WAKTU KONTAK PADA ADSORPSI Cd(II) MENGGGUNAKAN ADSORBEN KITIN TERFOSFORILASI DARI LIMBAH CANGKANG BEKICOT (Achatina fulica) - Hanjaya, Sasmita; Darjito, Darjito; Purwonugroho, Danar (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Abstract The adsorbent of Cd(II) ion from snail shell (Achatina fulica) waste had been made in this research. The aim of this research were to know the effect of pH and contact length on adsorption Cd(II) ions using phosphorylated chitin. The chitin from snail shell was characterized by FTIR and deacetylation degrees was counted. Bacth method was used to adsorp Cd(II) ion with pH variation (3, 4, 5, 6, 7) and contact length (30, 60, 90, 120, 150 minutes). Then the adsorption results was measured with Atomic Absorption Spectroscopy (AAS). The results showed that adsorbent had  deacetylation  degree  of  46.772%. Optimum  condition of pH and contact lengh were occured by 4 and 60 minutes with 92.3% and 75.3% respectively present of Cd(II) adsorption. Keywords: adsorption, cadmium, chitin, phosphorylated, snail shells.